Theaflavin-3-gallate, a natural antagonist for Hsp90: In-silico and in-vitro approach. (1st February 2022) - Bhadresha, Kinjal; Kumar, Sivakumar Prasanth; Brahmbhatt, Jpan; Patel, Chirag; Pandya, Pujan; Jain, Nayan; Rawal, Rakesh
Abstract: Poor prognosis and metastasis have been recognized as the major cause of breast cancer related deaths worldwide. Recent experimental evidence has shown that Hsp90, the prime chaperone, is overexpressed in many cancers and is responsible if reducing the 5-year survival rate of cancer patients. Therefore, targeted inhibition of Hsp90 may be a new and effective way to target cancer as well as enhancing therapeutic outcomes. In the present study, screening and simulation of potential natural compounds result in the identification of theaflavin-3-gallate as a promising inhibitory compound of Hsp90. Further in-vitro validation of the cytotoxic effect of theaflavin-3-gallate in human breast carcinoma cell line MCF7 and normal cell line MCF10A revealed that theaflavin-3-gallate significantly inhibited the cell proliferation of MCF7 cells whereas no cytotoxic effect was observed on MCF10A cells. We also found that theaflavin-3-gallate significantly induced programmed cell death by arresting cells in the G2/M phase of the cell cycle. A significant decrease in cell migration and colony formation by theaflavin-3-gallate treatment was also observed in MCF7 cells. Furthermore, theaflavin-3-gallate significantly downregulated the mRNA expression patterns of the HSP90, MMP9, VEGFA, and SPP1 genes. Collectively, our results demonstrated theaflavin-3-gallate as a potential natural Hsp90 inhibitor that can be used to enhance the therapeutic efficacy of existing breast cancer therapies and improve overall survival of breast cancer patients. Graphical abstract: Image 1 Highlights: HSP90 key modulators for pre-metastatic niche. Theaflavin-3-gallate inhibited cell migration through MMP signalling pathway. Theaflavin-3-gallate has potential effect on the HSP90 marker.